Making Social Media Activity Analytics Intelligible for Oneself and for Others: A “Boundary Object” Approach to Dashboard Design - Lambotte, François (Human Interface and the Management of Information: Information, Knowledge and Interaction Design, 2017)
Created in 2013, our laboratory works on the intelligibility of the activity of social media for others (e.a community animators) and for oneself (e.a member of the community) in a professional context. To bridge the gap between existing measures of activity, visualization of data and intelligibility of activity, we have set up a multidisciplinary team at the crossroads of these various players and knowledge. The goals of this team are to develop intelligible measures of the activity grouped together in a dashboard and to evaluate their contribution to the community’s dynamics. Inspired by the work of Star and Griesemer [16] on boundary objects and standardized methods, this paper aims to explain how we create, adapt and negotiate the current development of our dashboard’s prototype - conceived as a boundary object - sufficiently “robust” to achieve common objectives and “plastic enough” to meet the diverse interests of the different actors involved in the project.